Knowledge is the key… A grounded theory study exploring parent carer experiences of an Educational Psychology Service within pre-statutory stages of early intervention. - Winstanley, Jennifer (2023)
Parental engagement is recognised as a key factor in improving educational outcomes and achievement for young people (YP) (Harris & Goodall, 2011). Legislative policy and literature provide an on-going emphasis for involving parents and carers to support pupils with special educational needs and disabilities (SEND) (DfE, 2011; DfE & DoH, 2015). Educational Psychologists (EPs) are ideally placed to facilitate this, with parental engagement being a fundamental aspect of EP practice (Byrnes, 2012). Engaging collaboratively with parents and carers is integral to Educational Psychology Services (EPSs), yet challenges in achieving an effective partnership are widely reported (Hart, 2011; McGuiggan, 2021). The present study aims to extend the existing research landscape to better understand mechanisms that underpin parental engagement with a local authority (LA) EPS with hopes of improving practice and policy development to increase parental engagement to better support YP and wider service users.